THE ROLE OF GOOD CORPORATE GOVERNANCE IN REALIZING CORPORATE ACCOUNTABILITY: A CASE STUDY OF PT CIPUTRA DEVELOPMENT TBK - Flora Sania; Dini Sapira Br Sembiring; Sarah Obadiyah Ivana; Bunga Citra Lestari; Alya Rahma; Neng Sri Wardhani (Yayasan Multidimensi Kreatif, 2026)
This study examines the role of Good Corporate Governance (GCG) in realizing corporate accountability, using PT Ciputra Development Tbk, one of the largest listed property developers in Indonesia (stock code CTRA), as a case study. Accountability, one of the five GCG principles formulated by the National Committee on Governance Policy (KNKG), namely Transparency, Accountability, Responsibility, Independency, and Fairness (TARIF), requires clarity of function, implementation, and responsibility of every corporate organ so that management runs effectively. This research uses a descriptive qualitative method with a single case study approach, relying on secondary data obtained from the Company's Annual Reports for the 2023 and 2024 financial years, together with information published on the Company's official corporate governance pages. Data were collected through documentation studies and analyzed using content analysis, mapped against accountability indicators referring to the KNKG General Guidelines for Good Corporate Governance and applicable Financial Services Authority (OJK) regulations. The results show that PT Ciputra Development Tbk has established a complete governance structure consisting of the General Meeting of Shareholders, Board of Commissioners with Independent Commissioners, Board of Directors, Audit Committee, Nomination and Remuneration Committee, Corporate Secretary, and Internal Audit Unit, each of which carries a clearly defined accountability function. The Board of Commissioners and the Audit Committee, chaired by an Independent Commissioner, actively supervise management and coordinate with internal and external auditors, while the Board of Directors is held accountable through periodic reporting to the General Meeting of Shareholders. These findings indicate that the Company's governance practices are generally consistent with the accountability principle, although disclosure regarding the exact composition ratio of Independent Commissioners could be made more explicit in its public communication.